Analisis Retorika dan Nilai-Nilai Moral dalam Khutbah Quss bin Sa'idah al-Iyadi - Mujahid Abqori; Moh. Abdul Kholiq Hasan; Nanang Qosim (Ukazh : Journal of Arabic Studies, 2025)
This research analyzes the rhetorical richness and moral values contained within the Khutbah of Quss bin Sa'idah al-Iyadi, a pre-Islamic oration that holds significant relevance in the historical and cultural context of Arabia. This sermon offers a unique window into understanding the art of persuasion and ethical formation before the advent of Islam. The research aims to identify and interpret the rhetorical devices used and the moral values conveyed, then to connect them with classical and modern rhetorical theories as well as concepts of spiritual ethics. This study employs a qualitative approach with content analysis methodology on the text of the Khutbah of Quss bin Sa'idah al-Iyadi. Data was collected through literature review and analyzed hermeneutically to unearth profound meanings. The findings indicate that the sermon is rich in rhetorical elements such as repetition, figures of speech (tashbih, isti'arah), and rhetorical questions, all effectively employed to emphasize its message. Furthermore, fundamental moral values like monotheism, the transience of the world, the eternity of the afterlife, and divine justice were discovered. The novelty of this research lies in the integrated analysis of rhetorical aspects with moral values, highlighting how linguistic expertise served as a means for delivering transcendental ethics, and its implications for understanding the spiritual and linguistic roots in pre-Islamic society that formed the foundation for subsequent religious discourse.